The Outcome and Safety in Laparoscopic Common Bile Duct Exploration with Primary Suture versus T-Tube Drainage: A Meta-Analysis - Xianhua Ma; Shengbin Cai (Applied Bionics and Biomechanics)
Background. Sometimes, after choledochotomy, the common bile duct is closed with T-tube drainage for several weeks to prevent postoperative complications such as biliary fistula and stricture. But there has been controversy over the advantages of primary suture versus T-tube drainage. The purpose of our meta-analysis in laparoscopic common bile duct exploration is to appraise the efficacy and safety of T-tube drainage and primary suture. Methods. The literatures were searched by Web of Science, PubMed, Cochrane Library, OVID, and EMBASE between the year January 1, 2001 and February 28, 2021. Meta-analysis was performed by Stata 12. Results. Fourteen studies with 1,549 patients (827 vs. 722) were included in our study. The primary suture group had significant lesser operative time (P≤0.001), postoperative hospital stay (P≤0.001), hospital expenses (P≤0.001), intraoperative bleeding (P=0.001), and postoperative complications (P=0.006) than the T-tube drainage group. In postoperative bleeding (P=0.289), bile leakage (P=0.326), and bile duct stricture (P=0.750), there was no statistical difference. In the primary suture group, using single-arm synthesis, the bile leakage rate and the bile duct stricture rate were 0.07 vs. 0.04 and 0.00 vs. 0.00 in interrupted suture and continuous suture groups. The bile duct stricture rate was same in both groups, and the bile leakage rate was lower in the interrupted suture group. But the difference was not significant. Conclusion. The primary suture group had several advantages, including lesser operative time, postoperative complications, intraoperative bleeding, postoperative hospital stay, and hospital expenses. In bile leakage and bile duct stricture, the difference between the two groups was not significant. In the primary suture group, interrupted suture and continuous suture groups had similar bile leakage rate and bile duct stricture rate.